A Mixed-Methods Investigation of Australian Supermarkets’ Corporate Social Responsibility Commitments to Public Health: The Case of Supermarket Own Brand Foods - Pulker, Claire Elizabeth (Curtin University, 2019)
This PhD examined Australian supermarkets’ corporate social responsibility commitments that impact public health, and evidence of practical application, by analysing the contribution of supermarket own brand foods to Australian within-store food environments. A mixed-methods approach was used because so little was known about the topic. Findings from the eight included studies show how Australian supermarkets exert power over the food system and impact public health by the decisions they make.